Replacement of Asymmetric Synaptic Profiles in the Molecular Layer of Dentate Gyrus Following Cycloheximide in the Pilocarpine Model in Rats - Bittencourt, Simone; Covolan, Luciene; Hamani, Clement; Longo, Beatriz M.; Faria, Flávio P.; Freymuller, Edna; Ottersen, Ole P.; Mello, Luiz E. (Frontiers in Psychiatry, 2015)
Mossy fiber sprouting is among the best-studied forms of post-lesional synaptic plasticity and is regarded by many as contributory to seizures in both humans and animal models of epilepsy. It is not known whether mossy fiber sprouting increases the number of synapses in the molecular layer or merely replaces lost contacts. Using the pilocarpine model of status epilepticus to induce mossy fiber sprouting, and cycloheximide to block this sprouting, we evaluated at the ultrastructural level the number and type of asymmetric synaptic contacts in the molecular layer of the dentate gyrus. As expected, whereas pilocarpine-treated rats had dense silver grain deposits in the inner molecular layer (reflecting mossy fiber sprouting), pilocarpine+cycloheximide-treated animals did not differ from controls. Both groups of treated rats (Pilo group and CHX+Pilo group) had reduced density of asymmetric synaptic profiles (putative excitatory synaptic contacts), which was greater for cycloheximide-treated animals. For both treated groups the loss of excitatory synaptic contacts was even greater in the outer molecular layer than in the best studied inner molecular layer (in which mossy fiber sprouting occurs). These results indicate that mossy fiber sprouting tends to replace lost synaptic contacts rather than increase the absolute number of contacts. We speculate that the overall result is more consistent with restored rather than with increased excitability.